734. Efficacy of sulbactam-durlobactam (SUL-DUR) versus colistin in patients with extensively drug-resistant (XDR) and pan-drug resistant (PDR) Acinetobacter baumannii-calcoaceticus complex (ABC) infections. (15th December 2022) - Miller, Alita; McLeod, Sarah; Shapiro, Adam B; Rana, Khurram; Lewis, Drew; Poirier, Gabrielle; Chabas, Daria; Altarac, David
Abstract: Background: Acinetobacter baumannii-calcoaceticus complex (ABC) is a group of closely related species that cause serious infections associated with substantial mortality due in large part to very high antibiotic resistance rates and, consequently, a lack of effective therapies ( Lancet 2022: 399;629–655). ATTACK was a global, active-controlled Phase 3 trial conducted to evaluate the efficacy and safety of SUL-DUR versus colistin (COL) for patients with ABC infections. Clinical and microbiological outcomes of all CRABC m-MITT patients vs. those with XDR or PDR ABC infections in ATTACK. Methods: Part A was a blinded, randomized, non-inferiority study in ABC pneumonia or bacteremia. In Part B, patients who did not tolerate COL or had COL-resistant (R) ABC infections received SUL-DUR. All patients received imipenem/cilastatin as background therapy. Primary endpoint included 28-day all-cause mortality in Part A patients with carbapenem-resistant ABC at baseline (CRABC m-MITT). Clinical and microbiological outcomes were evaluated at End of Therapy (EOT), Test of Cure (TOC) and late follow-up (LFU) visits. COL-R was defined as MIC ≥ 4 µg/ml. MDR and XDR were defined according to Magiorakis et al (2012) CMI : 18, 268–81; PDR was defined as non-susceptibility to all approved agents (7 antibiotic classes) tested. Results: Of 149 baseline ABC isolates from CRABC m-MITT patients, 100% were (MDR), 129 (87%) were XDR and 14 (9.4%) were PDR. 19 (15%) of XDR and 10 (71%) of PDR ABC infections were in patients with bacteremia. 51% of XDR (N = 66) and all PDR ABC infections were in European patients. The SUL-DUR MIC50/90 against the XDR set was 2/4 µg/ml (range = 0.25 – 8 µg/ml). 13 (93%) PDR ABC were susceptible to SUL-DUR at ≤ 4 µg/mL, its preliminary breakpoint. Clinical and microbiological outcomes favoring SUL-DUR over COL were nearly identical in patients with XDR ABC infections as in the total population (Table 1). Of the 13 evaluable patients with PDR ABC infections treated with SUL-DUR in Part B, only one (7.7%) did not survive to Day 28 and 12 (92%) experienced clinical and microbiological cure at TOC. Conclusion: Patients enrolled in ATTACK had very high rates of XDR and PDR ABC infections, consistent with emerging global trends. Patients treated with SUL-DUR experienced better clinical and microbiological outcomes than those treated with COL, including those infected with XDR and PDR ABC. Disclosures: Alita Miller, PhD, Entasis Therapeutics: Employee Sarah McLeod, PhD, Entasis Therapeutics: Employee Adam B. Shapiro, Ph.D, Entasis Therapeutics: Employee|Entasis Therapeutics: Stocks/Bonds Khurram Rana, PharmD, Entasis Therapeutics: Employee|Entasis Therapeutics: Ownership Interest|Entasis Therapeutics: Stocks/Bonds Drew Lewis, MD, MTM&H, Entasis Therapeutics: employee|Entasis Therapeutics: employee|Entasis Therapeutics: Stocks/Bonds|Entasis Therapeutics: Stocks/Bonds Gabrielle Poirier, BS, Entasis Therapeutics: Ownership Interest|Entasis Therapeutics: Stocks/Bonds Daria Chabas, BS, Entasis Therapeutics: Ownership Interest|Entasis Therapeutics: Stocks/Bonds David Altarac, MD, MPA, Entasis Therapeutics: Ownership Interest|Entasis Therapeutics: Stocks/Bonds.